Exercise, weight maintenance, and nonalcoholic fatty liver disease risk: a Chinese cohort study - Yang, Chao; Yan, Peijing; Deng, Jiaqi; Li, Yujuan; Jiang, Xia; Zhang, Ben (Frontiers in Physiology, 2024)
Exercise has been reported to be associated with a reduced risk of nonalcoholic fatty liver disease (NAFLD), but there is no consensus on the role of weight changes in this association. This study aims to investigate whether the impact of exercise on NAFLD is mainly dependent on weight changes or is inherent to exercise itself.The study recruited 1671 Chinese NAFLD-free adults in 2019, and collected their exercise habits as well as three years of medical examination data including anthropometric measurements, blood biochemistry parameters, and liver ultrasound results. Univariate and multivariate logistic regression models were employed to examine the impact of exercise habits on NAFLD risk, with mediation analysis utilized to estimate the magnitude of the role of weight maintenance in the association between exercise and NAFLD.After adjusting for confounders, moderate to high-intensity exercisers were 1.56 times (95%CIs = 1.09 -2.22) more likely to successfully control their body weight, and therefore the weight-controlled group had a lower NAFLD risk of 34.9% (95%CIs = 21.8%-56.0%) compared to the weight-gain group. Mediation analysis reveals that exercise can significantly reduce the risk of NAFLD both through weight maintenance (37.1%) and independent of weight maintenance (62.9%).It might be more crucial to emphasize the adoption of regular moderate to high-intensity exercise 3 for preventing NAFLD in the general population, rather than solely focusing on weight maintenance.